Asymmetric multiple image elliptic curve cryptography. (January 2021) - Li, Wei; Chang, Xiangyu; Yan, Aimin; Zhang, Hongbo
Highlight: We propose a novel asymmetric multiple-image encryption method based on quick response code and elliptic curve cryptography. We conducted systematic evaluation of the robustness of the proposed method and found that the proposed method is able to resist different potential security attacks. The proposed method has a few significant advantages, such as a large fault tolerance, non-interference technique and high security. It can encrypt up to 16 images simultaneously which has great potential in user multiplexing and large image encryption/decryption. Abstract: A novel asymmetric multiple-image encryption method based on quick response code and elliptic curve cryptography is proposed through our research. In this new scheme, four quick response code images converted from four images and a random generated intensity key are used as the input for the elliptic curve cryptography image encryption system, which can yield two real number ciphertexts. The ciphertext image is further decrypted through a digital decryption scheme. The proposed system uses both public and private keys thus it is an asymmetric encryption system. The method can encrypt up to sixteen images simultaneously. Comprehensive numerical simulations have demonstrated the robustness and effectiveness of the encryption scheme.